The Managerial Leadership of School Principals on Teachers’ Professional Performance Competence - Agusalim, Agusalim; Ibanga, Isaac John; Yusnan, Muhammad; Saleh, Rachman; Riniati, Wa Ode (International Journal of Educational Management and Innovation, 2025)
Background/purpose. Managerial leadership of school principals is one of the key factors that determines the quality of education, particularly in improving teachers’ professional competence. Principals are not only responsible as administrators but also as leaders who must be able to plan, organize, implement, and supervise all school activities. This study aims to examine the extent to which the managerial leadership of principals influences teachers’ professional competence in junior high schools in Baubau City. The research focuses on four managerial aspects which are planning, organizing, actuating, and controlling, and their relationship to the improvement of teachers’ professional performance. Materials/methods. The research used a quantitative method with multiple linear regression analysis. The sample consisted of all junior high school principals in Baubau City, selected through a saturated sampling technique. The instrument was a questionnaire that had been tested for validity and reliability to ensure the accuracy of the data. Results. The findings shows that managerial leadership, including planning (β = 0.312; p = 0.004), organizing (β = 0.281; p = 0.007), implementing (β = 0.246; p = 0.021), and supervising (β = 0.271; p = 0.008), positively and significantly affects teachers’ professional competence. The model’s R² value of 0.659 indicates that 65.9 percent of the variation is explained by the principal’s leadership, while 34.1 percent is influenced by other factor. The four managerial functions contribute meaningfully to encouraging teachers to improve their professional performance, which in turn enhances the overall quality of education in schools. Conclusion. The study confirms that principals’ managerial leadership significantly enhances teachers’ professional competence. Through effective planning, organizing, actuating, and controlling, principals provide direction and support that encourage teachers to improve their performance, thereby strengthening the overall quality of education in junior high schools in Baubau City.